Photodegradation of Antibiotics by Noncovalent Porphyrin-Functionalized TiO(2) in Water for the Bacterial Antibiotic Resistance Risk Management - Gaeta, Massimiliano (Int J Mol Sci, 2020)
Antibiotics represent essential drugs to contrast the insurgence of bacterial infections in humans and animals. Their extensive use in livestock farming, including aquaculture, has improved production performances and food safety. However, their overuse can implicate a risk of water pollution and related antimicrobial resistance. Consequently, innovative strategies for successfully removing antibiotic contaminants have to be advanced to protect human health. Among them, photodegradation TiO(2)-driven under solar irradiation appears not only as a promising method, but also a sustainable pathway. Hence, we evaluated several composite TiO(2) powders with H(2)TCPP, CuTCPP, ZnTCPP, and SnT4 porphyrin for this scope in order to explore the effect of porphyrins sensitization on titanium dioxide. The synthesis was realized through a fully non-covalent functionalization in water at room conditions. The efficacy of obtained composite materials was also tested in photodegrading oxolinic acid and oxytetracycline in aqueous solution at micromolar concentrations. Under simulated solar irradiation, TiO(2) functionalized with CuTCPP has shown encouraging results in the removal of oxytetracycline from water, by opening the way as new approaches to struggle against antibiotic’s pollution and, finally, to represent a new valuable tool of public health.